Robotics / [filem jalur] - Lockwood, Wayne N.; Nelsen, Wayne; Fried Productions (Firm) (Bloomington, IL : Library Filmstrip Center, 1985)
Contents: 1. Robots in industry -- 2. Robot sub-systems -- 3. Operating parameters of robots -- 4. Applications of robot technology -- 5. Implementation of robots -- 6. Human factors in robotics